2017
DOI: 10.1177/0954408917743372
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory dissipative conjugate heat and mass transfer in chemically reacting micropolar flow with wall couple stress: A finite element numerical study

Abstract: High temperature non-Newtonian materials processing provides a stimulating area for process engineering simulation. Motivated by emerging applications in this area, the present article investigates the time-dependent free convective flow of a chemically-reacting micropolar fluid from a vertical plate oscillating in its own plane adjacent to a porous medium. Thermal radiative, viscous dissipation and wall couple stress effects are included. The Rosseland diffusion approximation is used to model uni-directional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…This is because of the fact that the diffusive species with higher values of Soret parameter   Sr has the tendency of increasing concentration profiles. gives the result for viscous incompressible fluid these trends can be seen in Shamshuddin et al, [58]. From this, it is observed that the velocity of the Newtonian fluid is greater than that of the micropolar fluid.…”
Section: Figures 34-37 Depict the Impact Of Dufour Number  supporting
confidence: 54%
“…This is because of the fact that the diffusive species with higher values of Soret parameter   Sr has the tendency of increasing concentration profiles. gives the result for viscous incompressible fluid these trends can be seen in Shamshuddin et al, [58]. From this, it is observed that the velocity of the Newtonian fluid is greater than that of the micropolar fluid.…”
Section: Figures 34-37 Depict the Impact Of Dufour Number  supporting
confidence: 54%
“…Bég et al [49] investigated analytically the radiative flux influence on unsteady gravity-driven optically-thick gray convection flow along an inclined plate with pressure gradient. Further studies include Mahmoud [50] (micropolar magnetic flow with thermal conductivity variation), Bég et al [51] (swirling Von Karman optically-thick MHD transpiring slip flow), El-Hakiem [52] (oscillatory hydromagnetic permeable convection), Shamshuddin et al [53] (reactive periodic dissipative micropolar thermo-solutal convection), Bég et al [54] (transient two-dimensional convective-radiative hydromagnetics), Hady et al [55] (radiative nanofluid dynamics) and Bhatti et al [56] (peristaltic pumping of electromagnetic two-phase flows).…”
mentioning
confidence: 99%
“…The main findings of the study are summarized as follows: The present study has been confined to Newtonian fluids. Future investigations will consider microstructural working fluids using the Eringen micropolar model [49] which are also of relevance to PEM fuel cell systems and efforts in this regard are currently underway.…”
Section: Discussionmentioning
confidence: 99%